Biological and chemical diversity of the Indonesian marine nudibranchs based on MS/MS molecular networking approach - Viqqi Kurnianda; Diah Astika Winahyu; Rian Firdaus; Erry Wahyudi; Musri Musman (Depik, 2020)
Abstract. The collection of 337 specimens of the Chromodoris species was conducted in Sabang island, Indonesia, from 2013 to 2019. The purpose of this study to investigate the biodiversity and their secondary metabolites related by molecular structures. There are 21 species together with the chemical diversity detected by MS/MS molecular networking approach. The results showed that the nudibranch species of C. willani and C. geometrica have the highest abundance species, while C. aureopurpurea has the lowest abundance species. The result of the chemical investigation showed that the class of diterpene derivatives was found from all specimens of Chromodoris genus in Sabang island, the western part of the Indonesian Archipelago.Keywords: Nudibranch, biodiversity, chemical diversity, MS/MS molecular networking, Chromodoris genus